Low-protein diets supplemented with glycine improves pig growth performance and meat quality: An untargeted metabolomic analysis - Jiang, Shengwang; Quan, Wei; Luo, Jie; Lou, Aihua; Zhou, Xihong; Li, Fengna; Shen, Qingwu W. (Frontiers in Veterinary Science, 2023)
For the purpose to improve pork eating quality, pigs were fed a normal diet (ND), a low protein diet (LPD) and a LPD supplemented with glycine (LPDG). Chemical and metabolomic analyses showed that LPD increased IMF deposition and the activities of GPa and PK, but decreased glycogen content, the activities of CS and CcO, and the abundance of acetyl-CoA, tyrosine and its metabolites in muscle. LPDG promoted muscle fiber transition from type Ⅱ to type Ⅰ, increased the synthesis of multiple nonessential amino acids, and pantothenic acid in muscle, which should contributed to the improved meat eating quality and growth rate. This study provides some new insight into the mechanism of diet induced alteration of animal growth performance and meat eatingmeat-eating quality. In addition, the study shows that dietary supplementation of glycine to LPD could be used to improved meat eating quality without impairment of animal growth.